Flow-mediated vasodilation as a diagnostic modality for vascular failure - Inoue, Teruo; Matsuoka, Hidehiro; Higashi, Yukihito; Ueda, Shin-Ichiro; Sata, Masataka; Shimada, Ken-Ei; Ishibashi, Yutaka; Node, Koichi (Hypertension research, 2008)
Vascular endothelial dysfunction represents an initial step of "vascular failure," which we have recently proposed as a comprehensive syndrome of failed vascular functions that extends from risk factors to established atherosclerotic disease. The early detection of vascular failure is essential in order to appropriately intervene and prevent its progression. Many efforts have been made to assess vascular endothelial function, and one of the most promising methods is the measurement of endothelium-dependent flow-mediated vasodilation (FMD) using high-frequency ultrasonographic imaging and transient occlusion of the brachial artery. The reactive hyperemia caused by the transient brachial arterial occlusion induces the release of local nitric oxide, resulting in vasodilation that can be quantified as an index of vasomotor function. The noninvasive nature of this technique allows repeated measurements over time to study the effectiveness of various interventions that may affect vascular health. Although there are technical and interpretive limitations of this technique, FMD-guided therapeutic approaches for vascular failure should contribute to the improvement of cardiovascular mortality and morbidity.